Heavy Metals in Marsh Clam (Polymesoda expansa) as Bioindicators for Pollution in Industrial and Sand Mining Area of Kelantan River Basin, Malaysia - Yusoff, Abdul Hafidz; Roslan, Nurul Nashuha; Chang, Chang Shen; Lazim, Azwan Mat; Nadzir, Mohd Shahrul Mohd; Oslan, Siti Nur Hazwani; Sulaiman, Ahmad Ziad; Ahmed, Minhaz Farid; Mohamed, Mazlan; Zakaria, Khairul Anam; Tan, Reasmey (Trends in Sciences, 2021)
Industrial and sand mining activities have severely degraded the water quality of the Kelantan River, as well as the river ecosystem. However, there have been inadequate studies on the effect of industrial and sand mining on organisms in the Kelantan River. Therefore, this study assessed the concentrations of Pb, Cd, Zn and Cu in the bivalves of genus (Polymesoda expansa) marsh clams from the Kelantan River tributaries, namely the Geting River and the Semarak River, which are located near to an industrial and a sand mining area, respectively. More than 50 marsh clams were collected at these sites. Heavy metals in marsh clams were extracted using aqua regia methods and analyzed using a Flame Atomic Absorption Spectrometer (FAAS). The mean concentrations of Pb, Cd, Zn and Cu at the Semarak River were 4.61, 2.16, 194 and 6.20 mg/kg, respectively. Accordingly, the concentrations at the Geting River were 4.43, 2.50, 196 and 7.90 mg/kg, respectively. The pattern of metal concentrations within the whole tissue of marsh clams from the Geting River and the Semarak River were in the following order: Zn > Cu > Pb > Cd (concentration in mg/kg). The mean concentration of selected metals (Zn, Cd, Pb) in the studied samples exceeded the permissible limit set by the Malaysia Food Safety and Food Regulation 1985, the Food and Agricultural Organization, the World Health Organization, the Ministry of Health Thailand, and the Food and Drug Administration of United States (USFDA). Therefore, continuous monitoring of these bioindicators is essential to minimize the increasing health risk for aquatic life, as well as in food sources for human consumption, in the Kelantan River Basin. HIGHLIGHTS Heavy metals in Marsh Clam (Polymesoda expansa) tissues shows higher concentration in the small and medium sizes compare to big size The concentration of heavy metals (Zn, Cd and Pb) in Marsh Clam (Polymesoda expansa) tissues have exceeded the permissible limit set by Food and Drug Administration of United States (USFDA) and Malaysia Food Safety and Food Regulation Monitoring of heavy metals in aquatic organisms especially near to industrial and sand mining areas should be conducted regularly to reduce the risk to human health GRAPHICAL ABSTRACT